Case Report: Successful Mechanical Thrombectomy in a Newborn With Basilar Artery Occlusion - Stracke, Christian Paul; Meyer, Lukas; Schwindt, Wolfram; Ranft, Alexander; Straeter, Ronald (Frontiers in Neurology, 2022)
Background Neonatal stroke remains a rare condition that has not yet been assessed in the field of endovascular treatment. Case We present the first case report of a successful mechanical thrombectomy in a newborn with a basilar occlusion the treatment was 14 hours after birth. Complete reperfusion of the basilar artery was achieved after the two thrombectomy maneuvers with stent retrievers. Imaging follow-up proved patency of the target vessel and at day 30, the patient showed no neurologic deficits. Conclusions Mechanical thrombectomy appears to be technically feasible and can be an individual option in selected cases to treat stroke in neonates with proven persistent proximal cerebral artery occlusion.